2011
DOI: 10.1002/ajpa.21407
|View full text |Cite
|
Sign up to set email alerts
|

Digit ratio (2D:4D) and rowing ergometer performance in males and females

Abstract: Fetal and adult testosterone may be vital in the establishment and maintenance of sex-dependent abilities associated with male physical competitiveness. It has been shown that digit ratio (2D:4D) is negatively associated with prenatal testosterone, and it is also negatively associated with ability in sports such as football, skiing, middle distance running, and endurance running, which are dependent upon an efficient cardiovascular system. The relationship between digit ratio and sports requiring high power (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 36 publications
4
59
2
4
Order By: Relevance
“…A lower digit ratio (2D:4D) correlates with performance in tests of strength [2] and endurance [3], and to performance in sporting activities such as rugby, soccer, surfing, skiing and running [4]. These relationships might be linked to the negative association between 2D:4D and T/E exposure in utero.…”
Section: Introductionmentioning
confidence: 98%
“…A lower digit ratio (2D:4D) correlates with performance in tests of strength [2] and endurance [3], and to performance in sporting activities such as rugby, soccer, surfing, skiing and running [4]. These relationships might be linked to the negative association between 2D:4D and T/E exposure in utero.…”
Section: Introductionmentioning
confidence: 98%
“…In many studies, 2D:4D finger ratio showed a negative correlation with physical fitness (Manning, 2002;Manning and Taylor, 2001). Low 2D:4D ratio is considered to be associated with high performance levels in many sports branches (Manning and Taylor, 2001;Manning, 2002;Paul et al 2006;Bennett et al 2010;Longman et al 2011). Sports performance depends on both an advanced cardiovascular system and muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the variance in 2 000 m performance being explained by fl uctuating asymmetry (9.5 % and 14.2 % in males and females, respectively) and the signifi cant improvement of 2 000 m performance associated with a standard deviation decrease of fl uctuating asymmetry (7.3 s and 10.2 s for males and females, respectively) suggests a potential use for fl uctuating asymmetry measurement as part of the talent identifi cation programs run by various national sporting bodies. When used in conjunction with measurements of digit ratio [7] the predictive power is further increased. This study has therefore shown that FA, when controlled for body size and diff erent levels of experience, is signifi cantly and negatively correlated with levels of attainment in a discipline requiring signifi cant energetic contributions from both aerobic and anaerobic systems.…”
Section: Male Rowersmentioning
confidence: 94%
“…Regression analysis, controlling for body size (height) and experience, revealed that for every standard deviation increase in fl uctuating asymmetry the 2 000 m time increased by 7.3 s, with 9.5 % of variance in ergometer performance being explained by fl uctuating asymmetry (r-squared = 0.095, p < 0.01). When right hand digit ratio data is incorporated [7] alongside fl uctuating asymmetry, height and years rowed, it is revealed that 51.5 % of variance in 2 000 m time can be explained by these factors (r-squared = 0.515). Colinearity has been tested for and no signifi cant relationships were found.…”
Section: Male Rowersmentioning
confidence: 98%
See 1 more Smart Citation